Differentiating Malignant from Tubercular Pleural Effusion by Cancer Ratio Plus (Cancer Ratio: Pleural Lymphocyte Count). (14th December 2016) - Verma, Akash; Dagaonkar, Rucha S.; Marshall, Dominic; Abisheganaden, John; Light, R. W.
Abstract : Background . We performed prospective validation of the cancer ratio (serum LDH : pleural ADA ratio), previously reported as predictive of malignant effusion retrospectively, and assessed the effect of combining it with "pleural lymphocyte count" in diagnosing malignant pleural effusion (MPE). Methods . Prospective cohort study of patients hospitalized with lymphocyte predominant exudative pleural effusion in 2015. Results . 118 patients, 84 (71.2%) having MPE and 34 (28.8%) having tuberculous pleural effusion (TPE), were analysed. In multivariate logistic regression analysis, cancer ratio, serum LDH : pleural fluid lymphocyte count ratio, and "cancer ratio plus" (ratio of cancer ratio and pleural fluid lymphocyte count) correlated positively with MPE. The sensitivity and specificity of cancer ratio, ratio of serum LDH : pleural fluid lymphocyte count, and "cancer ratio plus" were 0.95 (95% CI 0.87–0.98) and 0.85 (95% CI 0.68–0.94), 0.63 (95% CI 0.51–0.73) and 0.85 (95% CI 0.68–0.94), and 97.6 (95% CI 0.90–0.99) and 94.1 (95% CI 0.78–0.98) at the cut-off level of >20, >800, and >30, respectively. Conclusion . Without incurring any additional cost, or requiring additional test, effort, or time, cancer ratio maintained and "cancer ratio plus" improved the specificity of cancer ratio in identifying MPE in the prospective cohort.